2007
DOI: 10.1111/j.1365-2362.2007.01843.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid incorporation in endothelial cells and effects on endothelial nitric oxide synthase

Abstract: Among the fatty acids used, only modification of the membrane composition due to linoleic acid supply disturbed the basal enzymatic activity and Ser1177 phosphorylation of eNOS in a way that limited the role of histamine activation. Linoleic acid might involve the dysfunction of both eNOS basal activity and its phosphorylation status and may then contribute to an impaired vasodilatation in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…Obese subjects also have elevated levels of FFAs, which have been demonstrated to increase levels of oxidative stress and proinflammatory signaling and impair endothelial function (33). Further, there is evidence that increased levels of particular FFAs may directly inhibit endothelium‐derived NO synthase activity and its phosphorylation (34). Microvascular function is, however, only partially NO‐dependent, with several other mediators playing an important role (22).…”
Section: Discussionmentioning
confidence: 99%
“…Obese subjects also have elevated levels of FFAs, which have been demonstrated to increase levels of oxidative stress and proinflammatory signaling and impair endothelial function (33). Further, there is evidence that increased levels of particular FFAs may directly inhibit endothelium‐derived NO synthase activity and its phosphorylation (34). Microvascular function is, however, only partially NO‐dependent, with several other mediators playing an important role (22).…”
Section: Discussionmentioning
confidence: 99%
“…eNOS activity is modulated by the fatty acid composition of cell membranes and of caveolae [43], [44]. Thus induced changes in arterial membrane fatty acid composition may alter eNOS activity by changing the biophysical properties of arterial cell membranes and so contribute to differences in vaso-relaxation between maternal dietary groups.…”
Section: Discussionmentioning
confidence: 99%
“…This is a highly regulated process that requires leukocytes to the endothelium requires the interaction of integrin ligands on the leukocyte surface through immunoglobulin superfamily members, i.e., ICAM-1, ICAM-2 and VCAM-1, expressed on the endothelium [27]. Effects of OLA and LNA on endothelial cell expression of integrin ligands are conflicting: some authors demonstrated increases [15,28] and others found decreases in the expression of adhesion molecules [29][30][31]. These contrasting results possibly occurred due to differences in the experimental conditions such as the cell type, time of incubation and fatty acid concentrations used.…”
Section: Discussionmentioning
confidence: 99%